Effect of performing Collaborative Care Model on Controlling High Blood Pressure in patients referred to Semnan city's clinics, 2013. - Haghighat, Atefeh; Salehi, Shayesteh (Archives of Advances in Biosciences, 2015)
High blood pressure has become increasingly commonbetween people and also it takes a major risk factor for many diseases. The present study is done toperformthe collaborative care model in patients with high blood pressure. Hypertension is defined as: Systolic blood pressure (SBP) ≥140 mmHg or diastolic blood pressure (DBP) ≥90 mmHg .A collaborative care model is a native educating method based on patient's participation in the management of chronic disease. In this quasi-experimental study, 40 patients with high blood pressure (two equal groups of test and control) selected from two clinics in the city of Semnan in 2013, and they were evaluated using the targeted and simple random sampling.The checklists included demographic information (5 items), medical and smoking history (13 items), anthropometric parameters (3 items), laboratory measurements (6 items), diet (5 items), activities (7 items), dependent variables (5 items), cardiac complications (6 items), and frequency of doctor visits.The test group participated in intervention and participatory meetingsevery week. Collaborative care model, is comprised of4 stages; motivation, preparation, involvement, and evaluation over 3 months of intervention. Evaluation was based on the following criteria: Hypertensive patients(systolic blood pressure higher than 140 mmHg and diastolic blood pressureabove 90 mmHg, measured and approved in two different visits), to improvepatient health and knowledge, to decrease risk factors for disease,and to increase satisfaction and quality of health care services before and after intervention. Descriptive statistics, the independent t-test, and chi-square test were calculated at a significance level of 5%.Body mass index, triglyceride level, diastolic blood pressure, and salt intake declined in the test group after intermediation.Althoughthe consumption of bread and rice wasdecreased in the control group, but not in the test group.As previously described,performing the collaborative care model resulted in less catching high blood pressure, thus it can act as an efficient and cost-effective method for preventing and controlling high blood pressure.